Предмет: Алгебра,
автор: Orbualk
разложите на множители многочлен сейчас x^2+2x-3
Ответы
Автор ответа:
0
корни квадратного трехчлена -3 и 1. Поэтому (х+3)(х-1)
Автор ответа:
0
x^2+2x-3=0
По теореме Виета:
x1+x2=-p=-2
x1*x2=q=-3
x1=-3
x2=1
ax 2 + bx+ c = a ( x – x1 ) ( x – x2 )
x^2+2x-3=(x+3)(x-1)
Ответ: (x+3)(x-1).
По теореме Виета:
x1+x2=-p=-2
x1*x2=q=-3
x1=-3
x2=1
ax 2 + bx+ c = a ( x – x1 ) ( x – x2 )
x^2+2x-3=(x+3)(x-1)
Ответ: (x+3)(x-1).
Похожие вопросы
Предмет: Биология,
автор: varvaracat2010
Предмет: Математика,
автор: ogg8911
Предмет: Обществознание,
автор: Doshily
Предмет: Химия,
автор: irinalitvinova
Предмет: Право,
автор: JennySummer